Unveiling The Role of The Deep Sea In Mitigating Climate Change - Zhang, Miren (Transactions on Environment, Energy and Earth Sciences, 2024)
The deep sea, defined as marine areas of more than two hundred meters beneath the ocean surface, is an area full of scientific potential and mysteries. Linking the deep sea to climate change, one of the most significant issues of the current world, this essay examines and casts light on the role of the deep sea as a fundamental, nature-based mitigator of climate change. The results of this paper show that the role of the deep ocean in mitigating climate change remains promising based on the interpretation of its carbon sequestration, nutrient cycling and heat storage functions. The article focuses on the in-depth analysis and conclusions of the three major roles of the deep sea in mitigating climate warming. The resources and functions of the deep sea are extremely important to human society, and the national and international communities should pay more attention to the implementation of climate change mitigation methods through the use of the deep sea while raising awareness of the need to cultivate a sustainable and mutually beneficial relationship between human beings and the oceans.